Analisis Penerapan Latihan Fisik Pada Siswa Sekolah Dasar - Dea Khairum; Detya Mopalanda Sianipar; Diana Agatha Nainggolan; Ira Syafitri Siregar; Ismaina Hamda; Fajar Sidik Siregar (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Exercise is a body movement carried out by muscles in a planned, structured and repetitive manner, which involves the use of energy to improve fitness. According to the World Health Organization (WHO), school age children are children aged 7 to 15 years. Every individual has traits and characteristics or innate characteristics and characteristics obtained from environmental influences. The research method used in this research is descriptive analysis with a qualitative approach. This research uses a qualitative approach. Physical activity is an important aspect in the lives of elementary school age children. Elementary school age children still have limitations in terms of body endurance and ability to adapt to heavy training loads. Primary school age children are in a dynamic stage of development, so there is a need for specially designed training programs to increase their motivation and participation in physical activity. In this way, the benefits of physical activity can be maximized and support optimal growth and development for elementary school students. This collaborative effort will help create an environment that supports an active and healthy lifestyle from an early age.